2020
DOI: 10.3389/fmicb.2020.612474
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the Identification of an Earlier Pseudorabies Virus (PRV) Strain HLJ-2013 to the Evolution of Chinese PRVs

Abstract: Pseudorabies viruses (PRVs) pose a great threat to the pig industry of many countries around the world. Human infections with PRV have also been reported occasionally in China. Therefore, understanding the epidemiology and evolution of PRVs is of great importance for disease control in the pig populations and humans as well. In this study, we isolated a PRV designated HLJ-2013 from PRV-positive samples that had been collected in Heilongjiang, China, in 2013. The full genome sequence of the virus was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…The analysis results that showed the recombination between wild PRV strains and Bartha-K61 is possible, and more direct field evidence is ideally needed to support these results. Previous studies have demonstrated the high possibility of recombination between vaccine and clinically prevalent strains in different herpesviruses such as pseudorabies virus, varicella-zoster virus, bovine herpesvirus 1, infectious laryngotracheitis virus, and Marek’s disease virus [ 31 , 32 , 60 , 61 ]. Overall, these results indicate that recombination contributes to the evolution of novel PRV variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis results that showed the recombination between wild PRV strains and Bartha-K61 is possible, and more direct field evidence is ideally needed to support these results. Previous studies have demonstrated the high possibility of recombination between vaccine and clinically prevalent strains in different herpesviruses such as pseudorabies virus, varicella-zoster virus, bovine herpesvirus 1, infectious laryngotracheitis virus, and Marek’s disease virus [ 31 , 32 , 60 , 61 ]. Overall, these results indicate that recombination contributes to the evolution of novel PRV variants.…”
Section: Resultsmentioning
confidence: 99%
“…The genomic intermolecular recombination between two PRV strains has been reported in natural infection conditions by two studies [ 29 , 30 ]. Recently, several studies revealed the potential recombination between Bartha-K61 and virulent PRV strains, suggesting that recombination might have involved PRV evolution during the pandemic in China [ 31 , 32 ]. Additionally, recombination between virulent field viruses and the live vaccine strain was recorded in bovine herpesvirus 1 and infectious laryngotracheitis viruses [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though Bartha-K61 vaccine can provide complete protection against the classical strain ( 10 , 19 ), some factors may contribute to vaccine failure, such as co-infection with PRRSV ( 21 ), indicating that the PR eradication or control cannot only rely on vaccination. Additionally, PRV recombinant isolates derived from genotype I and genotype II strains or classical and variant strains were often identified ( 26 , 27 ). Thus the prevalence of classic strains and variant PRVs and wide application of the attenuated vaccine strain Bartha-K61 may increase the possibility of PRV genomic recombination, which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Except for GD1802, which might be introduced abroad, the other three strains all have a relationship with recombination. Ye et al found that SC was a recombinant of an endemic Chinese strain and a Bartha-vaccine-like strain [ 25 ]; Bo et al found that the JSY13 strain was a recombination of the PRV variant JSY7 strain and the Bartha K61 vaccine strain [ 26 ]; Liu et al found that the HLJ-2013 strain is probably a recombination of three origins: a yet unknown parent strain, a European-origin strain, and a Chinese-origin strain [ 27 ]. Besides these, Huang et al found that the FJ62 variant strain was the recombination between the PRV genotype I strain from wild boar and genotype II strain from domestic pig [ 28 ].…”
Section: The Outbreaks and The Genomic Evolution Of Prv Variantsmentioning
confidence: 99%